Inclusion Complexes of Some Substituted 4-Thiazolidinones with Activating and Deactivating Group - Dash, Simanchal (Asian Journal of Chemistry, 2019)
Some substituted 4-thiazolidinones have been prepared by taking 2-hydrazinobenzothiazole as a staring material. Polar solvent water makes less solubility of these compounds. Hence inclusions of compounds are prepared by taking suitable ratio of compound and β-cyclodextrin. The purpose of this work is to synthesize more soluble and more bioaccesible compounds. The synthesized compounds and their inclusions are known from the study of their thermodynamic properties and spectral characteristics (UV, IR and NMR). Pharmaceutical activity of the compounds and inclusion can be performed by using the bacteria namely E. coli, S. aureus and P. vulgaris. Considering and discussing all the matters, it has been found that inclusion formation shows more antibacterial activity than simple compound.